The Practicality of Popular Scientific Book of Pteridophytes Diversity in Tabanio Beach Forest, Tanah Laut District, South Borneo - Nurlita Nurlita; Yudi Firmanul Arifin; Atiek Winarti (Master Program of Biology Education, Universitas Lambung Mangkurat, 2021)
Learning using popular scientific books based on the local potential of an area is one solution that can be used to overcome students' lack of reading interest in learning due to limited learning resources in the Pteridophyta concept. This study aims to describe the practicality of a popular scientific book Diversity of the Tabanio Coastal Forest Pteridophyta. The method used is development research with the Tessmer formative test. The results showed that popular scientific books that have been developed obtained student responses with an average of 94.3% with very good criteria and the results of implementing the use of popular scientific books with an average of 92.6% with very good criteria. This shows that a popular scientific book Diversity of Tabanio Coastal Forest Pteridophyta is very practical to be used as an enrichment material in learning Low Plant Botany.Abstrak Pembelajaran dengan menggunakan buku ilmiah populer (BIP) berdasarkan potensi lokal yang dimiliki sebuah daerah merupakan salah satu solusi yang dapat digunakan untuk mengatasi kurangnya minat membaca mahasiswa dalam pembelajaran karena keterbatasan sumber belajar pada konsep Pteridophyta. Penelitian ini bertujuan untuk mendeskripsikan kepraktisan buku ilmiah populer Keanekaragaman Pteridophyta Hutan Pantai Tabanio. Metode yang digunakan adalah penelitian pengembangan dengan uji formatif Tessmer. Hasil penelitian menunjukkan buku ilmiah populer yang telah dikembangkan memperoleh hasil respons mahasiswa dengan rata-rata sebesar 94,3% dengan kriteria sangat setuju dan hasil keterlaksanaan penggunaan buku ilmiah populer dengan rata-rata sebesar 92,6% dengan kriteria sangat baik. Hal tersebut menunjukkan bahwa buku ilmiah populer Keanekaragaman Pteridophyta Hutan Pantai Tabanio sangat praktis digunakan sebagai bahan pengayaan dalam pembelajaran Botani Tumbuhan Rendah.